Evaluation of remote services and patient satisfaction - a qualitative study - Laskowski, Jakub; Kister, Klaudia; Mazur, Magdalena; Rektor, Natalia; Małolepsza, Aleksandra; Zach-Źródlak, Monika; Rosa, Lidia; Czechowska, Julia; Bronst, Paulina; Szabrańska, Anna (Journal of Education, Health and Sport, 2023)
BACKGROUND: Telemedicine is among the most modern branches of medicine. In the field of mental health, telepsychiatry makes it possible to replace the traditional conversation with a specialist with an e-visit. With the development of remote services, qualitative studies evaluating this type of service have begun to be conducted. The studies involve both patients and clinicians. The purpose of this study is to show the advantages perceived by patients who use telepsychiatry services, as well as concerns that may discourage further use of digital therapy. The study also includes an evaluation of telemedicine services. Material and methods: The authors created a proprietary structured questionnaire that consisted of two parts. The first concerned sociodemographic data, while the second addressed the subject of patients’ evaluation with the use of telepsychiatry services, possible difficulties during e-visits and satisfaction with this type of consultation. Before completing the survey, patients filled out informed consent. The survey was conducted from November 2022 to May 2023. Results: The final group of respondents was formed by 432 people. The largest group of respondents were patients with the diagnosis: affective disorders - 24.07%. The vast majority of respondents - 81.94% - indicated the possibility of teleportation from anywhere in the world as the greatest advantage of telepsychiatry. Another advantage is not having to take time off from work or school - 78.94%. Major disadvantages included: limited treatment methods (71.07% of respondents), made it more difficult to build a therapeutic alliance 59.03%, privacy and cybersecurity concerns 43.06%. Overall, patients rate telepsychiatry well - 66% of respondents were satisfied. Conclusions: Telepsychiatry is well rated among most patients. More research is needed to develop clear guidelines for digital therapy. Patients receiving remote therapy should be screened for the development of addiction to mobile devices and the Internet.